Los estudios internacionales en América Latina : problemas fundamentales - Muñoz, Heraldo (Estudios Internacionales, 1980)
This essay analyzes the current state of international studies as an academic specialty in Latin America, paying special attention to the methodological and substantive aspects of the field, and the key obstacles to its development. Regarding the methodological, we focus, first, on the question of the applicability of the unidisciplinary versus interdisciplinary approach; second, in the problem of units and levels of analysis; third, in the "traditionalism" versus "science" debate; and, finally, in the matter of the normative aspects of international studies. The geographical and functional orientations of international studies in the region are identified and, finally, the main obstacles of institutional, economic, socio-political and ethical origin to the development of international studies in Latin America are examined.